Public engagement through public service advertisements for health care awareness during early COVID-19 in Pakistan - Elareshi, Mokhtar; Habes, Mohammed; Ali, Sana; Waheeb Attar, Razaz (Frontiers in Communication, 2024)
The way information disseminated in the early period of COVID-19 led the world to confusion and an unprecedented public health crisis. This paper examines the relationships between public engagement through public service advertisements (PSA) and the effectiveness of health care awareness during early COVID-19. To explore such a relationship and mainly public perceptions, we conducted a very early survey (n=200) using an online convenience sampling procedure with different age groups in Sahiwal, Pakistan. Data were analysed using the PLS-SEM software to measure such a relationship. We find that PSA were perceived as a vital platform, which has an impact on public perceptions towards taking precautionary measures during the early pandemic. Importantly, PSA have a strong impact on spreading health awareness in Pakistan. Policymakers and health care professionals should grasp and acknowledge the significance of media content influence to enhance health awareness including the role of PSAs in health care. This comprehension may motivate the adoption of practices and policies in the health sector, contributing to the known ‘new normal’, ensuring their continuity even beyond the COVID-19 era.